Financial Performance Analysis of Small Plastic Manufacturing Businesses in Indonesia - A Case Study Approach - Kumar, Sachin; Nigam, Namita (Ushus Journal of Business Management, 2025)
This case study examines the financial performance of small and medium-sized plastic manufacturing enterprises in Indonesia. The research has a sample size of five companies. The investigation spans seven years, encompassing annual financial statements from January 2016 to December 2022. This case study focuses on analysing the financial performance of Small Plastic Manufacturing Businesses in Indonesia using various financial statement analysis methodologies such as vertical and horizontal ratio analysis, DuPont analysis, Peer Analysis, and hypothesis testing. The case study's findings indicate that business liquidity of few companies is improving generally, but profitability growth is stagnating.